Cyclic loading of an idealized clay‐filled fault: comparing hydraulic flow in two clay gouges. Issue 3 (27th April 2016) - Cuss, R. J.; Graham, C. C.; Wiseall, A. C.; Harrington, J. F.
Abstract: The flow of water along discontinuities, such as fractures or faults, is of paramount importance in understanding the hydrogeology of many geological settings. An experimental study was undertaken comprising two experiments on a 30° slip‐plane filled with kaolinite or Ball Clay gouge using a bespoke Angled Shear Rig (ASR). The gouge was initially loaded in equal step changes in vertical stress, followed by unloading of the sample in similar equal steps. This was followed by reloading to a new maximum stress, followed by unloading; the test history was therefore load‐unload‐reload‐unload (LURU). The transmissivity of the kaolinite and Ball Clay gouge showed a power‐law relationship with vertical stress. The LURU history showed considerable hysteresis, with flow effectively unchanged during unloading, even when vertical stress was close to zero. Reloading resulted in flow similar to that seen during unloading suggesting that the unloading‐reloading path is similar to the rebound‐reconsolidation line in classic soil mechanics. These observations show the importance of stress history on fracture flow; consideration of just the current stress acting upon a fracture may result in inaccuracies of predicted hydraulic flow. Once a new stress maximum was achieved the transmissivity of the fracture continued to reduce. No significant variation was seen in the flow response of kaolinite and Ball Clay gouge suggesting that the inclusion of illite and quartz did not have a significant influence on the form of the relationship between stress and flow, i.e. both described by a power‐law.